Impact of cigarette smoking on impaired insulin secretion and insulin resistance in Japanese men: The Saku Study - Morimoto, Akiko (Wiley-Blackwell, 2012)
AIMS/INTRODUCTION: To assess the impact of smoking on impaired insulin secretion and insulin resistance in Japanese men. MATERIALS AND METHODS: This study included 1,199 men aged 30–79 years without diabetes, impaired insulin secretion and insulin resistance at baseline who underwent a comprehensive medical check‐up between April 2006 and March 2007 at Saku Central Hospital. Smoking status was categorized as current, ex‐smoker and never‐smoker. Insulinogenic index and homeostasis model assessment‐insulin resistance were determined using a standard 75‐g oral glucose tolerance test. The Japan Diabetes Society criteria were used to define impaired insulin secretion and insulin resistance. Participants were followed up until March 2011. RESULTS: A total of 449 and 99 men developed impaired insulin secretion and insulin resistance during 3,403 and 4,092 person‐years follow up, respectively. The multivariable‐adjusted hazard ratios (HRs) for impaired insulin secretion were 1.06 (95% confidence interval [CI] 0.84–1.33) in ex‐smokers and 1.95 (95% CI 1.44–2.63) in current smokers compared with never‐smokers after adjustment for age, familial history of diabetes, alcohol consumption, exercise, systolic blood pressure, triglyceride, γ‐glutamyltransferase, waist circumference, leukocyte count, changes in smoking status and changes in waist circumference. The number of pack‐years was positively associated with the risk for impaired insulin secretion in a dose‐dependent manner (P‐values for trend <0.001). The multivariable‐adjusted HRs for insulin resistance were 0.95 (95% CI 0.56–1.61) in ex‐smokers and 1.11 (95% CI 0.67–1.79) in current smokers compared with never‐smokers. CONCLUSIONS: Cigarette smoking is a modifiable risk factor for impaired insulin secretion. The findings might also be important for other Asian populations, which have low insulin secreting ability.